2011
DOI: 10.2172/1028528
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Different Economic Performance Metrics on the Perceived Value of Solar Photovoltaics

Abstract: NOTICEThis report was prepared as an account of work sponsored by an agency of the United States government. Neither the United States government nor any agency thereof, nor any of their employees, makes any warranty, express or implied, or assumes any legal liability or responsibility for the accuracy, completeness, or usefulness of any information, apparatus, product, or process disclosed, or represents that its use would not infringe privately owned rights. Reference herein to any specific commercial produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 18 publications
1
33
0
Order By: Relevance
“…Combining the above information with the figures quoted in (International Energy Agency 2009) and (Drury et al 2011), where average annual PV system costs was reported as $3.85/W and $3.91/W respectively, we believe it is reasonable to assume the costs of PV modules and installation are $4.00/W in this case study.…”
Section: Module Costmentioning
confidence: 59%
See 3 more Smart Citations
“…Combining the above information with the figures quoted in (International Energy Agency 2009) and (Drury et al 2011), where average annual PV system costs was reported as $3.85/W and $3.91/W respectively, we believe it is reasonable to assume the costs of PV modules and installation are $4.00/W in this case study.…”
Section: Module Costmentioning
confidence: 59%
“…The methodology used here is broadly consistent with that used in other broadly similar studies such as (Kirby and Davison 2010;Drury et al 2011;Davison et al 2012); no exact comparison study to this has been published. We also test the robustness of these results via the following parameter sensitivity study.…”
Section: Sensitivity Analysismentioning
confidence: 95%
See 2 more Smart Citations
“…Then some methods commonly used to assess the economic profitability analysis of investment projects in renewable energies are reviewed [8,10,52,57,60,61]. Namely, expressions to calculate the IRR, the net present value (NPV), the benefit-to-cost ratio (BCR), and the discounted payback time (DPBT) are proposed.…”
Section: Introductionmentioning
confidence: 99%